Components and Strategic Routes of Corporate Transformations - Biland Sadek (International Journal of Business and Social Science Research, 2024)
In response to modern-day disruptions and to maintain competitiveness and viability, companies embark on corporate transformation journeys to enhance performance and boost organizational health. When transformations succeed, they fundamentally boost a company’s key business drivers. This article is a first step in providing prescriptive literature to transforming companies that they can use to navigate their journey. The article defines the three components of corporate transformations business model transformation, digital-enabled transformation, and organizational transformation - and their interdependencies. The study is based on the systematic review of literature available on the components of corporate transformations which is mostly unidimensional and leads to the consolidation of the components into a framework. It also describes the strategic routes of corporate transformations (mesa-transformation and meta-transformation). The framework is applicable for academic research and for practitioners when diagnosing companies, strategizing their transformations, and planning their transformation journeys.